Pengaruh Sifat Konduktivitas Termal Material Isolator (Kayu, Karet Dan Styrofoam) Terhadap Perpindahan Panas Dan Daya Keluaran Sistem Generator Thermoelectric: Effect of Thermal Conductivity Properties of Insulating Materials (Wood, Rubber and Styrofoam) on Heat Transfer and Output Power of a Thermoelectric Generator System - Vazri Muharom; Rifky (Universitas Muhammadiyah PROF. DR. HAMKA Fakultas Teknik – Program Studi Teknik Mesin, 2022)
The purpose of this experiment is to get insulator from all three material (wood, rubber and styrofoam) which will produce a good heat insulator on thermoelectric. This research was conducted on the open floor at the Faculty of Engineering, University Muhammadiyah Prof. DR. HAMKA in Jakarta, Indonesia between March-October 2019 by using 3 thermoelectric. The hope of this experiment is to produce the most electricity from the three materials.